MicroRNA-96 regulates RGC-5 cell growth through caspase-dependent apoptosis - Wang, Shaopeng (Int J Clin Exp Med, 2014)
Purpose: This study is to investigate functional role of microRNA 96 (miR-96) in regulating cell survival and caspase-dependent apoptosis in rat retinal ganglion cell line RGC-5 cells. Method: RGC-5 cells were cultured in vitro. Lentiviral vectors of miR-96 inhibitor, miR-96 mimics and non-specific miRNA were applied. The effects of up-regulating or down-regulating miR-96 on cell survival, apoptosis and activation of apoptosis-related caspase proteins were assessed by MTT assay, TUNEL staining and western blotting analysis, respectively. Direct binding of miR-96 and its suspected target caspase protein, caspase 2 (Casp-2), was examined by luciferase reporter assay. Endogenous CASP2 gene was then silenced by siRNA in RGC-5 cells. The effect of down-regulating CASP2 on miR-96 mediated apoptosis in RGC-5 was assessed by western blotting and TUNEL staining. Results: Lentivirus mediated- miR-96 up-regulation significantly reduced RGC-5 cell viability 12 hours after transfection, whereas miR-96 down-regulation had no effect on RGC-5 cell survival up to 72 hours. Up-regulating miR-96 induced significant apoptosis in RGC-5 cells, whereas down-regulating miR-96 had little effect on RGC-5 apoptosis. Western blotting analysis demonstrated that RGC-5 apoptosis induced by overexpressing miR-96 is associated with activation of caspase proteins, including caspase-2, 3, 9. Luciferase reporter assay confirmed that Casp-2 was directly bound by miR-96 in RGC-5 cells, and siRNA-regulated silencing of CASP2 gene rescued the apoptosis in RGC-5 induced by over-expressing miR-96. Conclusion: miR-96 is an important regulator on RGC-5 cell survival and apoptosis, possibly through Casp-2.